2018
DOI: 10.1016/j.pedneo.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Screening of congenital hypothyroidism in preterm, low birth weight and very low birth weight neonates: A systematic review

Abstract: Evidence from different screening programs indicated that the rate of congenital hypothyroidism (CH) was higher in pre-term and low-birth-weight (LBW) newborns than normal ones. Incomplete development of hypothalamic-pituitary axis in this group of neonates results in the delayed rise of TSH and missing cases with CH. Hence, there is a great need for a practicable systematic screening method for proper diagnosis of CH in this group of neonates. In this review, we systematically reviewed papers with the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 41 publications
(44 reference statements)
1
60
0
8
Order By: Relevance
“…CH and, in particular, mild CH are more common in some risk categories such as preterm or ill neonates [12], small for gestational age infants [13], children born after in vitro fertilization (IVF) [14], and in multiple pregnancies [15]. In these categories of neonates, the initial screening tests may be inappropriate or provide normal results, and therefore the European Society for Pediatric Endocrinologist (ESPE) guidelines [2] suggest a strategy of second screening, at about 2 weeks of age or 2 weeks after the first screening test.…”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…CH and, in particular, mild CH are more common in some risk categories such as preterm or ill neonates [12], small for gestational age infants [13], children born after in vitro fertilization (IVF) [14], and in multiple pregnancies [15]. In these categories of neonates, the initial screening tests may be inappropriate or provide normal results, and therefore the European Society for Pediatric Endocrinologist (ESPE) guidelines [2] suggest a strategy of second screening, at about 2 weeks of age or 2 weeks after the first screening test.…”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
“…In a recent systematic review, Hashemipour et al [12] recommend repeating the screening test in preterm, LBW, and VLBW infants at the age of 2, 6, and 10 weeks by measuring TSH and FT4 levels simultaneously and considering TSH of 10 mIU/L as the cutoff level for positive and suspicious cases.…”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
“…Opinions vary regarding the recommended rescreening time for TFT, and these variances can range between 2 and 6 weeks after birth 14,3537) . Hashemipour et al 37) reviewed documentation on the screening process of preterm congenital hypothyroidism and suggested that repeated screening is necessary. A TSH level of 10 mU/L was defined as the positive cutoff level; a TSH level of 10 to…”
Section: Risk Factorsmentioning
confidence: 99%
“…Ayrıca, RDS olan hastalarda daha prematüre olmalarından dolayı solunum destek süresi de uzun bulunmuştur (19). Çalışmamızda daha prematüre bebeklerde doğum sonrası TSH yüksekliği ile daha düşük sT4 düzeyi ve RDS oranı prematüreliğin getirdiği bir sonuçtur (8,20,21).…”
Section: Introductionunclassified